Online Education as Perceived by Teachers and Students - Gautam, Pitamber (Prithvi Journal of Research and Innovation, 2022)
The domain of formal education has now been impacted by digitized technology. The modes and manners of education have been inclined to the virtual world. The online mode of education took a radical surge in the aftermath of the COVID-19 pandemic as an alternative resort. Nonetheless, numerous controversies and gruesome voices loomed in the academic realm due to abrupt transitioning beyond ample preparations. Nepali academia adopted virtual mode of education amidst the bewilderment. The government, as well as private agencies, seemed reserved in exploring the lived perceptions of the teachers and students. Against this backdrop, this paper has attempted to delve into the teachers' and the students' experiences; two most vital and immediate stakeholders in the pedagogical process. To address this objective, this study has adopted the phenomenological design under the qualitative research approach. The information was collected from six teachers and nine students who were involved in three distinct campuses. The purposively selected informants were interviewed and three live classes were observed to obtain valid information. The collected data were processed, analyzed, interpreted and presented into three relevant themes viz. views expressed, challenges faced and the limitations detected. The results show that the recently executed online mode of education, despite being a temporal demand of the new era, consists of numerous facets to be ameliorated. Lack of ICT training to pedagogues, recursive electric power-cut; unavailability, poor bandwidth and instability of the internet; inappropriate curricula, lack of online and offline study resources are the prime issues to be addressed by the stakeholders.